IMPLEMENTATION OF GOOD ZAKAT GOVERNANCE IN ZIS MANAGEMENT: A CASE STUDY OF BAZNAS, BARRU DISTRICT - Rabiatul Adawiyah; Andi Bahri; Zainal Said; Hannani Hannani; Suarning Suarning (Ad Deenar: Jurnal Ekonomi dan Bisnis Islam, 2026)
This study aims to analyze the implementation of Good Zakat Governance (GZG) in the management of zakat, infaq, and alms (ZIS) at BAZNAS Barru Regency. The background of this study is based on the increase in ZIS collection every year, although it is still faced with internal obstacles such as limited human resources and field coordination, as well as external challenges in the form of the community's economic conditions. This study focuses on the application of GZG principles that include transparency, accountability, responsibility, independence, and fairness in the planning, implementation, and supervision of ZIS management. The research method used is a qualitative descriptive approach with a case study approach, through interviews, observations, and documentation at BAZNAS Barru Regency. The results show that the principle of transparency is implemented through a SIMBA-based reporting system and PSAK 109, and accountability is realized through internal and external audits. Independence is strengthened by cooperation between BAZNAS, local governments, and the private sector, while the principle of justice is reflected in the distribution of zakat according to the needs of mustahik in various regions. However, limited human resources, low community participation, and a manual verification system remain the main obstacles. This research contributes to strengthening zakat governance at the regional level and enriches academic studies on the implementation of Good Zakat Governance in Indonesia.